Non-linear surges and extreme wind-waves in Port Phillip Bay under existing and future mean sea levels - Tran, Huy Quang; Ayala Cruz, Franklin; McCarroll, Jak; Babanin, Alexander (Frontiers in Marine Science, 2024)
This study investigates non-linear surges and extreme wind-wave patterns in Port Phillip Bay (PPB), Victoria, Australia, under both current and projected mean sea level scenarios, utilising a combined wave-circulation modelling system (SCHISM-WWMIII). The validated computational model was employed to simulate 32 years of hindcasts and was applied to five distinct mean sea level (MSL) scenarios (existing, 0.5 m, 0.8 m, 1.1 m, and 1.4 m). By analysing data extracted from 24 different stations in the bay at a depth of 2 m, this research provides insights into the potential impacts of increasing MSL on extreme surges and wind-waves. Under the current scenario, the results indicate that both surges and wave patterns are significantly influenced by seasonal wind patterns. In the context of rising mean sea levels, this research reveals that while surges exhibit a degree of resilience to changes in MSL, the wave field is more vulnerable to such variations. The non-linear response of the wave field to increasing MSL further complicates the scenario. For instance, there is an unequal response in the median of the annual maximum significant wave height (Hs) corresponding to the rising MSL from 0 m to 0.5 m and from 0.5 m to 0.8 m, which is expected due to wave breaking triggered by alterations in water depth. Specifically, in the context of the increase in MSL from 0 m to 0.5 m, the median annual maximum Hs at 12 locations remains unchanged. However, increasing MSL from 0.5 m to 0.8 m increases the median annual maximum Hs by up to 0.36 m, accounting for 70% of the total increase in the median annual maximum Hs when MSL rises from 0 m to 1.4 m at the same locations. This study found that intensification in the median of annual maximum Hs occurs only in locations where the values exceed 1.0 m. This suggests that areas with higher median Hs values are more prone to experiencing significant variations. In contrast, stations with a median annual maximum Hs below the 1.0 m threshold exhibit only minor increases in the annual maximum Hs.